Cold atmospheric plasma in combination with mechanical treatment improves osteoblast growth on biofilm covered titanium discs. (June 2015) - Duske, Kathrin; Jablonowski, Lukasz; Koban, Ina; Matthes, Rutger; Holtfreter, Birte; Sckell, Axel; Nebe, J. Barbara; von Woedtke, Thomas; Weltmann, Klaus Dieter; Kocher, Thomas
Abstract: Treatment of implants with peri-implantitis is often unsuccessful, because an instrumented implant surface and residual microbial biofilm impedes re-osseointegration. The application of cold atmospheric plasma (CAP) could be a simple and effective strategy to overcome the inherent problems of peri-implantitis treatment. CAP is able to destroy and eliminate bacterial biofilms. Additionally, it increases the wettability of titanium, which supports cellular attachment. In this study, the behaviour of osteoblasts on titanium discs was analysed after treatment of bacterial biofilms with CAP, brushing, or a combination of both. A human plaque biofilm was cultured on titanium discs. Treatment with a brush (BR), 1% oxygen/argon CAP (PL), or brushing combined with CAP (BR + PL) was used to eliminate the biofilm. Discs without biofilm (C), autoclaved biofilm (AUTO) and untreated biofilm (BIO) served as controls. Subsequently, human osteoblastic cell growth (MG-63) was observed after 1 and 24 h. Biofilm remnants on BR and PL impaired osteoblastic cell development, whereas the BR + PL provided an increased area of osteoblastic cells. A five-day cell growth was only detectable on BR + PL treated discs. The combination of established brushing and CAP application may be a promising strategy to treat peri-implantitis.